SWOT Analysis of Indonesia's Trade in Services in Facing The ASEAN Trade in Services Agreement (ATISA) - Sambuaga, Jerry; Ningsih, Endah Ayu (Buletin Ilmiah Litbang Perdagangan, 2024)
The liberalization of services within the Association of Southeast Asian Nations (ASEAN) has been a key focus since the ASEAN Framework Agreement on Services (AFAS) was signed in 1995. This effort reached a new milestone by introducing the ASEAN Trade in Services Agreement (ATiSA) in 2019, which seeks to enhance further the integration and liberalization of the services sector across ASEAN member states (AMS). ATiSA aims to create a stable and predictable environment for service trade by reducing discriminatory regulatory barriers and increasing transparency. This study explores the best strategy for Indonesia to leverage the benefits of ATiSA by conducting a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The distributed questionnaires are filled out by 43 individual respondents from 19 government institutions representing nine ministry or national agencies, seven private sectors, and two academic institutions. The SWOT results show that Indonesia can take the Strengths-Opportunity strategy to benefit from ATiSA implementation. To maximize the strength, moderate support is still needed to regulate and develop certified workers. Meanwhile, opportunities to win the ASEAN market include considerable market potential, investment opportunities, enhanced international trade, and positive consumer perception of Indonesian services driven by quality, technology, and digital marketing strategies.